Recent Updates on Interaction Studies and Drug Delivery of Antimalarials with Serum Albumin Proteins - Azeem, Kashish; Irfan, Iram; Rashid, Qudsia; Singh, Shailja; Patel, Rajan; Abid, Mohammad (Current Medicinal Chemistry, 2024)
This review focuses on recent trends in the binding study of various antimalarial agents with serum albumins in detail. Serum albumin has a significant role in the transport of drugs and endogenous ligands. The nature and magnitude of serum albumin and drug interactions have a tremendous impact on the pharmacological behavior and toxicity of that drug. Binding of drug to serum albumin not only controls its free and active concentration, but also provides a reservoir for a long duration of action. This ultimately affects drug absorption, distribution, metabolism, and excretion. Such interaction determines the actual drug efficacy as the drug action can be correlated with the amount of unbound drug. With the advancement in spectroscopic techniques and simulation studies, binding studies play an increasingly important role in biophysical and biomedical science, especially in the field of drug delivery and development. This review assesses the insight we have gained so far to improve drug delivery and discovery of antimalarials on the basis of a plethora of drug-serum protein interaction studies done so far.
Keywords: serum albumin